Genetic Diversity and Association of Low-Density Simple Sequence Repeat Markers with Yield Traits in Wheat Under Salt Stress - Shugao Fan; Jiawei Wu; Ying Zhao (Agronomy)
Wheat exhibits moderate tolerance to salinity. The increasing salinization of arable land poses a significant risk to future wheat production. Therefore, it is imperative to expedite the genetic breeding of wheat for enhanced salt tolerance. This study investigates the genetic and phenotypic diversity of 90 wheat varieties under salt stress, utilizing a comprehensive approach involving trait distribution analysis, hierarchical clustering, kinship estimation, and low-density association analysis. The phenotypic analysis of key agronomic traits revealed significant variability in traits such as leaf area index, canopy temperature, grain area, dry weight, harvest index, grain yield, and tiller number. Most traits exhibited a near-normal distribution, with a few parameters showing skewed or bimodal distributions, indicating the presence of subpopulations with distinct trait profiles. The hierarchical clustering analysis identified five distinct genetic clusters among the wheat varieties, highlighting the complex genetic relationships and variations in salt stress tolerance. Kinship estimates further confirmed the presence of genetic divergence among the accessions, with a majority showing weak or null relationships. Statistical models for association analysis revealed the effectiveness of the Generalized Linear Mixed Model (GLMM) in detecting a greater number of significant genetic markers associated with key agronomic traits, with the GLMM explaining a higher proportion of phenotypic variation. The findings underline the importance of genetic diversity in wheat breeding programs aimed at improving salt stress tolerance and agronomic performance. These results provide valuable insights for future breeding strategies, focusing on the optimization of key traits and marker-assisted selection for the development of salt-tolerant wheat cultivars.